2010
DOI: 10.1111/j.1365-2672.2009.04562.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the co-circulation of enteric viruses in sewage and in the population of Greater Cairo

Abstract: Aims:  To characterize major enteric viruses (enterovirus, rotavirus, norovirus, astrovirus and adenovirus) in the sewage of Greater Cairo and to compare the results with clinical data collected during the same period. Methods and Results:  Seventy‐two sewage samples from two waste water treatment plants were collected from April 2006 through February 2007. Enteroviruses, noroviruses (NoVs) and rotaviruses (RVs) were detected by RT‐PCR in 22%, 18% and 8·3% of the samples, respectively. No adenovirus and astrov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
51
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 49 publications
10
51
2
Order By: Relevance
“…In this study, G1P [8], G3P [8], and G1P [4] were the dominant genotypes among Egyptian children (29.7%, 27.0%, and 18.9%, respectively). These findings are in partial agreement with previous studies conducted in Egypt (10)(11)(12)17), and in complete agreement with global studies, which reported P [8], P [6], and P [4] as the most common P genotypes with frequent combinations of G1P [8], G4P [8], G3P [8], G9P [8], G2P [4], and G9P [6] as the dominant genotypes globally (23). On the other hand, enteric adenovirus type 41 was the most common genotype in Cairo.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In this study, G1P [8], G3P [8], and G1P [4] were the dominant genotypes among Egyptian children (29.7%, 27.0%, and 18.9%, respectively). These findings are in partial agreement with previous studies conducted in Egypt (10)(11)(12)17), and in complete agreement with global studies, which reported P [8], P [6], and P [4] as the most common P genotypes with frequent combinations of G1P [8], G4P [8], G3P [8], G9P [8], G2P [4], and G9P [6] as the dominant genotypes globally (23). On the other hand, enteric adenovirus type 41 was the most common genotype in Cairo.…”
Section: Discussionsupporting
confidence: 83%
“…However, no astrovirus infection was observed. These findings are relatively similar to the detection rates reported in Egypt and other countries for the epidemiology of rotavirus and adenovirus (associated with acute diarrhea) in children below five years old (4,5,10,11,17).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In Africa, the prevalence of NoVs has been investigated in both clinical (Mans et al 2010(Mans et al , 2014Hassine-Zaafrane et al 2013;Huynen et al 2013;) and environmental settings (Kamel et al 2010;Kiulia et al 2010;Sdiri-Loulizi et al 2010;Gibson 2011;Mans et al 2013;Murray et al 2013). Noroviruses have also been detected in shellfish collected along the Mediterranean Sea and Atlantic Coast of Morocco (Benabbes et al 2013).…”
Section: Introductionmentioning
confidence: 99%